Geometry of the Valgus Knee: Contradicting the Dogma of a Femoral-Based Deformity. (March 2017) - Eberbach, Helge; Mehl, Julian; Feucht, Matthias J.; Bode, Gerrit; Südkamp, Norbert P.; Niemeyer, Philipp
Background: Realignment osteotomies of valgus knee deformities are usually performed at the distal femur, as valgus alignment is considered to be a femoral-based deformity. This dogma, however, has not been proven in a large patient population. Valgus malalignment may also be caused by a tibial deformity or a combined tibial and femoral deformity. Purpose: The purposes of this study were (1) to analyze the coronal geometry of patients with valgus malalignment and identify the location of the underlying deformity and (2) to investigate the proportion of cases that require realignment osteotomy at the tibia, the femur, or both locations to avoid an oblique joint line. Study Design: Cross-sectional study; Level of evidence, 3. Methods: The analysis included 420 standing full-leg radiographs of patients with valgus malalignment (mechanical femorotibial angle [mFTA], ≥4°). A systematic analysis of the coronal leg geometry was performed including the mFTA, mechanical lateral distal femoral angle (mLDFA), mechanical medial proximal tibial angle (mMPTA), and joint-line convergence angle (JLCA). The localization of the deformity was determined according to the malalignment test described by Paley, and patients were assigned to 1 of 4 groups: femoral-based valgus deformity, tibial-based valgus deformity, femoral- and tibial-based valgus deformity, or intra-articular/ligamentary–based valgus deformity. Subsequently, the ideal osteotomy site was identified with the goal of a postoperative change of the joint line of two different maximum values, ±2° and ±4°, from its physiological varus position of 3°. Results: Measurements of the coronal alignment revealed a mean (±SD) mFTA of 7.4° ± 4.3° (range, 4°-28.2°). The mean mLDFA and mean mMPTA were 84.8° ± 2.4° and 90.9° ± 2.6°, respectively. The mean JLCA was 1.2° ± 3.1°. The majority (41.0%) of valgus deformities were tibial based, 23.6% were femoral based, 26.9% were femoral and tibial based, and 8.6% were intra-articular/ligamentary based. To achieve a straight-leg axis and an anatomic postoperative joint line with a tolerance of ±4°, the ideal site of a corrective osteotomy was tibial in 55.2% of cases and femoral in 19.5% of cases. A double-level osteotomy would be necessary in 25.2% of cases. With a tolerance of ±2°, the ideal osteotomy site was the proximal tibia in 41.0% of cases and the distal femur in 13.6% of cases; a double-level osteotomy would be necessary in 45.5% of cases. Conclusion: In contrast to the widespread belief that valgus malalignment is usually caused by a femoral deformity, this study found that valgus malalignment was attributable to tibial deformity in the majority of patients. In addition, a combined femoral- and tibial-based deformity was more common than an isolated femoral-based deformity. As a clinical consequence, varus osteotomies to treat lateral compartment osteoarthritis must be performed at the tibial site or as a double-level osteotomy in a relevant number of patients to avoid an oblique joint line.